Assessment of rapeseed oil body (oleosome) lipolytic activity as an effective predictor of emulsion purity and stability. (30th June 2020) - De Chirico, Simone; di Bari, Vincenzo; Romero Guzmán, María Juliana; Nikiforidis, Constantinos V.; Foster, Tim; Gray, David
Highlights: Oil bodies from Brassica napus seeds were assessed for hydrolytic activity. Carry-over of oil body hydrolytic activity is affected by the recovery medium used. Most of hydrolytic activity is reduced with a short-time thermal treatment (95 °C). The integrity of oil bodies is not affected by the thermal treatment applied. Reducing hydrolytic activity enhances the physical stability over storage. Abstract: The lipolytic activity in oil body creams as affected by recovery and washing protocols was investigated. The effect of thermal treatment on the hydrolytic activity and physical stability of fresh and aged (up to 30 days) oil body emulsions was studied. The use of alkaline pH solutions (9.5) to soak and grind rapeseeds were more effective reducing the contamination of oil body material from seed proteins/enzymes, compared with neutral pHs. Soaking and grinding seeds with a NaHCO3 solution (0.1 M, pH 9.5) yielded oil bodies with a similar composition to those prepared in urea (9 M); however, the physical stability over storage was compromised due to the presence of hydrolytic enzymes. Heating a dispersion of oil bodies for 6 mins at 95 °C did not alter the physical properties of oil bodies and significantly reduced lipolytic activity (>90% enzyme inactivation), resulting in a stable emulsion.